Reflections On Nature In The Scientific And Philosophical Views Of Beruni And Ibn Sina - Bekzod Ibragimov (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
This article presents the scientific conclusions related to the natural science hypotheses found in the intellectual correspondence (Q&A letters) between Abu Rayhan Beruni and Abu Ali Ibn Sina — two key figures considered vital sources in the development of socio-philosophical thought during the first Renaissance period in Uzbekistan. The article also explores the social and philosophical aspects of natural philosophy as reflected in the views of Beruni and Ibn Sina.